Compound, molded body, and cured product of compound
Patent Information
- Application Number
- JP2021574121
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-01-30
- Filing Date
- 2021-01-28
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2041-01-28
AI Technical Summary
【0009】 本発明によれば、耐リフロー性に優れる成形体を形成できるコンパウンド、それを用いた成形体、及びコンパウンドの硬化物が提供される。
Smart Images

Figure 0007639712000001 
Figure 0007639712000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a compound, a molded article, and a cured product of the compound. [Background technology]
[0002] Compounds containing metal powders and resin compositions are used as raw materials for various industrial products depending on the physical properties of the metal powders. For example, compounds are used as raw materials for inductors, sealing materials, electromagnetic shields (EMI shields), bonded magnets, etc. (see Patent Document 1 below). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2014-13803 A Summary of the Invention [Problem to be solved by the invention]
[0004] When manufacturing industrial products from a compound, the compound and a metal member are adhered to each other, the compound is cured to produce a molded body, and the molded body is then heated. In the process of heating the molded body, cracks are likely to form in the molded body due to the difference in thermal expansion coefficient between the cured compound and the metal member, steam explosions inside the package, etc. Therefore, it is necessary to improve the reflow resistance of the molded body.
[0005] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a compound capable of forming a molded article having excellent reflow resistance, a molded article using the same, and a cured product of the compound. [Means for solving the problem]
[0006] A compound according to one aspect of the present invention comprises a metal powder and a resin composition containing an epoxy resin and a phenol resin, wherein the epoxy resin comprises a first epoxy resin having a biphenylene aralkyl skeleton and a second epoxy resin having an epoxy equivalent smaller than that of the first epoxy resin, and the phenol resin comprises a first phenol resin having a biphenylene aralkyl skeleton and a second phenol resin having a hydroxyl equivalent smaller than that of the first phenol resin, and the metal powder content is 90% by mass or more and less than 100% by mass.
[0007] A molded article according to one aspect of the present invention contains the above-mentioned compound.
[0008] A cured product of a compound according to one aspect of the present invention is a cured product of a compound comprising a metal powder and a resin composition containing an epoxy resin and a phenol resin, the cured product of the compound having a metal powder content of 90% by mass or more and less than 100% by mass, a bending strength at 250°C of 4.6 MPa or more, a bending modulus at 250°C of less than 1.0 GPa, and a value obtained by dividing the bending strength by the bending modulus of 9.5 × 10 -3 That's all. Effect of the Invention
[0009] According to the present invention, there are provided a compound capable of forming a molded article having excellent reflow resistance, a molded article using the compound, and a cured product of the compound. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Preferred embodiments of the present invention will be described below, however, the present invention is not limited to the following embodiments.
[0011] [Compound] The compound according to the present embodiment includes a metal powder and a resin composition containing an epoxy resin and a phenolic resin. The metal powder may contain at least one selected from the group consisting of a simple metal, an alloy, an amorphous powder, and a metal compound. The resin composition may further contain other components in addition to the epoxy resin and the phenolic resin. The resin composition may further contain a curing accelerator, a mold release agent, an additive, and the like. The resin composition may be a component that may include an epoxy resin, a phenolic resin, a curing accelerator, a mold release agent, and an additive, and may be the remaining components (non-volatile components) excluding an organic solvent and a metal powder. The additive is the remaining component of the resin composition excluding a resin, a mold release agent, a curing agent, and a curing accelerator. The additive is, for example, a coupling agent, a flame retardant, a lubricant, and the like. The compound may be a powder (compound powder).
[0012] The compound may comprise a metal powder and a resin composition attached to the surface of each metal particle constituting the metal powder. The resin composition may cover the entire surface of the particle, or may cover only a part of the surface of the particle. The compound may comprise an uncured resin composition and a metal powder. The compound may comprise a semi-cured product of the resin composition (e.g., a B-stage resin composition) and a metal powder. The compound may comprise both an uncured resin composition and a semi-cured product of the resin composition. The compound may be composed of a metal powder and a resin composition.
[0013] The content of the metal powder in the compound is 90% by mass or more and less than 100% by mass with respect to the total mass of the compound. If the content of the metal powder is high, it is difficult to ensure the releasability of the molded body, and the workability tends to be poor. From the viewpoint of the magnetic properties of the molded body, the content of the metal powder is preferably 92% by mass or more, more preferably 94% by mass or more, even more preferably 95% by mass or more, and particularly preferably 96% by mass or more. The upper limit of the content of the metal powder may be 99% by mass or less, 98% by mass or less, or 97.5% by mass or less.
[0014] (Resin composition) The resin composition according to the present embodiment contains a specific epoxy resin as a thermosetting resin, which can improve the fluidity, storage stability, and moldability of the compound. The epoxy resin contains a first epoxy resin having a biphenylene aralkyl skeleton and a second epoxy resin having an epoxy equivalent smaller than that of the first epoxy resin.
[0015] By including the first epoxy resin in the resin composition, the elastic modulus of a molded article formed from the compound can be reduced, and reflow resistance can be improved. The epoxy equivalent of the first epoxy resin is preferably 240 g / eq or more and 300 g / eq or less, more preferably 250 g / eq or more and 290 g / eq or less, and even more preferably 260 g / eq or more and 280 g / eq or less.
[0016] The content of the first epoxy resin in the resin composition may be 20 to 80 mass %, 30 to 70 mass %, or 40 to 60 mass % based on the total mass of the epoxy resins.
[0017] As a commercially available product of the first epoxy resin, for example, a biphenylene aralkyl type epoxy resin (NC-3000 manufactured by Nippon Kayaku Co., Ltd.) may be used.
[0018] The resin composition containing the second epoxy resin tends to increase the mechanical strength of the molded body. The epoxy equivalent of the second epoxy resin is preferably 130 g / eq or more and less than 240 g / eq, more preferably 140 g / eq or more and 230 g / eq or less, and even more preferably 150 g / eq or more and 220 g / eq or less.
[0019] The second epoxy resin may be, for example, a resin having two or more epoxy groups in one molecule, or a polyfunctional epoxy resin having three or more epoxy groups. The second epoxy resin may be, for example, a stilbene type epoxy resin, a diphenylmethane type epoxy resin, a sulfur atom-containing epoxy resin, a novolac type epoxy resin, a dicyclopentadiene type epoxy resin, a salicylaldehyde type epoxy resin, a naphthol-phenol copolymer type epoxy resin, an epoxidized product of an aralkyl type phenol resin, a bisphenol type epoxy resin, a biphenyl type epoxy resin, an epoxy resin containing a bisphenol skeleton, a glycidyl ether type epoxy resin of an alcohol, a glycidyl ether type epoxy resin of a paraxylylene and / or metaxylylene modified phenol resin, a glycidyl ether type epoxy resin of a terpene modified phenol resin, or the like. and at least one selected from the group consisting of glycidyl ether type epoxy resins, cyclopentadiene type epoxy resins, glycidyl ether type epoxy resins of polycyclic aromatic ring-modified phenolic resins, glycidyl ether type epoxy resins of naphthalene ring-containing phenolic resins, glycidyl ester type epoxy resins, glycidyl or methylglycidyl type epoxy resins, alicyclic type epoxy resins, halogenated phenol novolac type epoxy resins, ortho-cresol novolac type epoxy resins, hydroquinone type epoxy resins, trimethylolpropane type epoxy resins, and linear aliphatic epoxy resins obtained by oxidizing an olefin bond with a peracid such as peracetic acid.
[0020] From the viewpoint of excellent fluidity, the second epoxy resin may be at least one selected from the group consisting of orthocresol novolac type epoxy resins, phenol novolac type epoxy resins, bisphenol type epoxy resins, epoxy resins having a bisphenol skeleton, salicylaldehyde novolac type epoxy resins, and naphthol novolac type epoxy resins.
[0021] The second epoxy resin may be a crystalline epoxy resin. Although the molecular weight of the crystalline epoxy resin is relatively low, the crystalline epoxy resin has a relatively high melting point and excellent fluidity. The crystalline epoxy resin (highly crystalline epoxy resin) may be, for example, at least one selected from the group consisting of hydroquinone type epoxy resin, bisphenol type epoxy resin, thioether type epoxy resin, and biphenyl type epoxy resin.
[0022] Commercially available crystalline epoxy resins include, for example, Epicron 860, Epicron 1050, Epicron 1055, Epicron 2050, Epicron 3050, Epicron 4050, Epicron 7050, Epicron HM-091, Epicron HM-101, Epicron N-730A, Epicron N-740, Epicron N-770, Epicron N-775, Epicron N-776, Epicron N-777, Epicron N-778, Epicron N-779, Epicron N-780, Epicron N-781, Epicron N-782, Epicron N-783, Epicron N-784, Epicron N-785, Epicron N-786, Epicron N-787, Epicron N-788, Epicron N-789, Epicron N-781, Epicron N-782, Epicron N-783, Epicron N-784, Epicron N-785, Epicron N-785, Epicron N-786, Epicron N-787, Epicron N-788, Epicron N-789 ... N-865, Epicron HP-4032D, Epicron HP-7200L, Epicron HP-7200, Epicron HP-7200H, Epicron HP-7200HH, Epicron HP-7200HHH, Epicron HP-4700, Epicron HP-4710, Epicron HP-4770, Epicron HP-5000, Epicron HP-6000, N50 0P-2, and N500P-10 (product names manufactured by DIC Corporation); NC-3000, NC-3000-L, NC-3000-H, NC-3100, CER-3000-L, NC-2000-L, XD-1000, NC-7000-L, NC-7300-L, EPPN-501H, EPPN-501HY, EPPN-502H, EOCN-1020, EO It may be at least one selected from the group consisting of CN-102S, EOCN-103S, EOCN-104S, CER-1020, EPPN-201, BREN-S, BREN-10S (all of which are trade names manufactured by Nippon Kayaku Co., Ltd.); and YX-4000, YX-4000H, YL4121H, and YX-8800 (all of which are trade names manufactured by Mitsubishi Chemical Corporation).
[0023] The resin composition according to the present embodiment contains a specific phenolic resin as a curing agent, which can improve the fluidity, storage stability, and moldability of the compound. The phenolic resin contains a first phenolic resin having a biphenylene aralkyl skeleton and a second phenolic resin having a smaller hydroxyl equivalent than that of the first phenolic resin.
[0024] The resin composition contains the first phenolic resin, which reduces the elastic modulus of the molded body and improves reflow resistance. The hydroxyl equivalent of the first phenolic resin is preferably 140 g / eq or more and 230 g / eq or less, more preferably 150 g / eq or more and 220 g / eq or less, and even more preferably 160 g / eq or more and 210 g / eq or less.
[0025] The content of the first phenol resin in the resin composition may be 20 to 80 parts by mass, 30 to 70 parts by mass, or 40 to 60 parts by mass with respect to 100 parts by mass of the epoxy resin.
[0026] Commercially available biphenylene aralkyl phenol resins may be, for example, MEHC-7851SS, MEHC-7841-4S, etc. manufactured by Meiwa Kasei Co., Ltd.
[0027] The resin composition contains the second phenolic resin, and the mechanical strength of the molded body is easily increased. The hydroxyl equivalent of the second phenoxy resin is preferably 80 g / eq or more and less than 140 g / eq, more preferably 90 g / eq or more and 130 g / eq or less, and even more preferably 100 g / eq or more and 120 g / eq or less.
[0028] The second phenolic resin may be at least one selected from the group consisting of, for example, aralkyl-type phenolic resin, dicyclopentadiene-type phenolic resin, salicylaldehyde-type phenolic resin, novolac-type phenolic resin, copolymerized phenolic resin of benzaldehyde-type phenol and aralkyl-type phenol, paraxylylene- and / or metaxylylene-modified phenolic resin, melamine-modified phenolic resin, terpene-modified phenolic resin, dicyclopentadiene-type naphthol resin, cyclopentadiene-modified phenolic resin, polycyclic aromatic ring-modified phenolic resin, and triphenylmethane-type phenolic resin. Commercially available products of the second phenolic resin may be, for example, HE910-09 manufactured by Air Water Inc., HP-850N manufactured by Hitachi Chemical Co., Ltd., and the like.
[0029] The ratio of the active group (phenolic OH group) in the curing agent that reacts with the epoxy group in the epoxy resin may be preferably 0.5 to 1.5 equivalents, more preferably 0.6 to 1.4 equivalents, and even more preferably 0.7 to 1.2 equivalents relative to 1 equivalent of the epoxy group in the epoxy resin. When the ratio of the active group in the curing agent is within the above range, the fluidity of the compound is likely to be improved.
[0030] The curing accelerator is not limited as long as it is a composition that reacts with the epoxy resin to accelerate the curing of the epoxy resin. The curing accelerator may be, for example, a phosphorus-based curing accelerator, an imidazole-based curing accelerator, or a urea-based curing accelerator. The resin composition contains a curing accelerator, which can improve the moldability and releasability of the compound. In addition, the resin composition contains a curing accelerator, which can improve the mechanical strength of a molded body (e.g., electronic parts) produced using the compound, and improve the storage stability of the compound under high temperature and high humidity environments.
[0031] Examples of the phosphorus-based curing accelerator include phosphine compounds and phosphonium salt compounds.
[0032] As a commercially available imidazole curing accelerator, for example, at least one selected from the group consisting of 2MZ-H, C11Z, C17Z, 1,2DMZ, 2E4MZ, 2PZ-PW, 2P4MZ, 1B2MZ, 1B2PZ, 2MZ-CN, C11Z-CN, 2E4MZ-CN, 2PZ-CN, C11Z-CNS, 2P4MHZ, TPZ, and SFZ (all of which are product names manufactured by Shikoku Chemical Industry Co., Ltd.) may be used.
[0033] The urea-based curing accelerator is not particularly limited as long as it is a curing accelerator having a urea group, but from the viewpoint of improving storage stability, it is preferable to use an alkylurea-based curing accelerator having an alkylurea group. Examples of the alkylurea-based curing accelerator having an alkylurea group include aromatic alkylurea and aliphatic alkylurea. Examples of commercially available alkylurea-based curing accelerators include U-CAT3512T (trade name, manufactured by San-Apro Co., Ltd., aromatic dimethylurea) and U-CAT3513N (trade name, manufactured by San-Apro Co., Ltd., aliphatic dimethylurea). Among these, aromatic alkylurea is preferable because it has a moderately low cleavage temperature and is easy to efficiently cure the compound.
[0034] The amount of the curing accelerator is not particularly limited as long as it is an amount that can obtain a curing acceleration effect. However, from the viewpoint of improving the curability and fluidity of the resin composition when absorbing moisture, the amount of the curing accelerator may be preferably 0.1 parts by mass or more and 30 parts by mass or less, more preferably 1 part by mass or more and 15 parts by mass or less, relative to 100 parts by mass of the epoxy resin. The content of the curing accelerator is preferably 0.001 parts by mass or more and 5 parts by mass or less, relative to 100 parts by mass of the total mass of the epoxy resin and the phenolic resin. When the amount of the curing accelerator is less than 0.1 parts by mass, it is difficult to obtain a sufficient curing acceleration effect. When the amount of the curing accelerator is more than 30 parts by mass, the storage stability of the compound is easily reduced. However, even if the amount and content of the curing accelerator are outside the above range, the effect of the present invention can be obtained.
[0035] The coupling agent improves the adhesion between the resin composition and the metal element-containing particles constituting the metal powder, and improves the flexibility and mechanical strength of the molded body formed from the compound. The coupling agent may be, for example, at least one selected from the group consisting of silane-based compounds (silane coupling agents), titanium-based compounds, aluminum compounds (aluminum chelates), and aluminum / zirconium-based compounds. The silane coupling agent may be, for example, at least one selected from the group consisting of epoxy silane, mercapto silane, amino silane, alkyl silane, ureido silane, acid anhydride silane, and vinyl silane. The resin composition may contain one of the above coupling agents, or may contain multiple of the above coupling agents.
[0036] The resin composition may contain a compound having a siloxane bond (siloxane compound) because the molding shrinkage rate of the compound is easily reduced and the heat resistance and voltage resistance of the molded body are easily improved. The siloxane bond is a bond containing two silicon atoms (Si) and one oxygen atom (O), and may be represented by -Si-O-Si-. The compound having a siloxane bond may be a polysiloxane compound.
[0037] For the purpose of improving the environmental safety, recyclability, moldability, and low cost of the compound, the compound may contain a flame retardant. The flame retardant may be, for example, at least one selected from the group consisting of bromine-based flame retardants, phosphorus-based flame retardants, hydrated metal compound-based flame retardants, silicone-based flame retardants, nitrogen-containing compounds, hindered amine compounds, organometallic compounds, and aromatic engineering plastics. The resin composition may contain one of the above flame retardants, or may contain multiple of the above flame retardants.
[0038] When a molded body is formed from the compound using a mold, the resin composition may contain a wax. The wax increases the fluidity of the compound during molding (e.g., transfer molding) of the compound and also functions as a mold release agent. The wax may be at least one of a fatty acid such as a higher fatty acid and a fatty acid ester.
[0039] Examples of the wax include fatty acids such as montanic acid, stearic acid, 12-oxystearic acid, and lauric acid, and esters thereof; fatty acid salts such as zinc stearate, calcium stearate, barium stearate, aluminum stearate, magnesium stearate, calcium laurate, zinc linoleate, calcium ricinoleate, and zinc 2-ethylhexanoate; and fatty acid salts such as stearic acid amide, oleic acid amide, erucic acid amide, behenic acid amide, palmitic acid amide, lauric acid amide, hydroxystearic acid amide, methylene bisstearic acid amide, ethylene bisstearic acid amide, ethylene bislauric acid amide, distearyl adipate amide, ethylene bisoleic acid amide, dioleyl adipate amide, N-stearyl stearic acid amide. fatty acid esters such as butyl stearate; alcohols such as ethylene glycol and stearyl alcohol; polyethers such as polyethylene glycol, polypropylene glycol, polytetramethylene glycol and modified products thereof; polysiloxanes such as silicone oil and silicone grease; fluorine compounds such as fluorine-based oil, fluorine-based grease, and fluorine-containing resin powder; and waxes such as paraffin wax, polyethylene wax, amide wax, polypropylene wax, ester wax, carnauba wax, and microwax.
[0040] (metal powder) The metal powder (metal element-containing particle) may contain at least one selected from the group consisting of, for example, a metal element, an alloy, and a metal compound. The metal element-containing powder may be, for example, at least one selected from the group consisting of a metal element, an alloy, and a metal compound. The alloy may contain at least one selected from the group consisting of a solid solution, a eutectic, and an intermetallic compound. The alloy may be, for example, stainless steel (Fe-Cr alloy, Fe-Ni-Cr alloy, etc.). The metal compound may be, for example, an oxide such as ferrite. The metal powder may contain one type of metal element or multiple types of metal elements. The metal element contained in the metal powder may be, for example, a base metal element, a precious metal element, a transition metal element, or a rare earth element. The compound may contain one type of metal element-containing powder, or may contain multiple types of metal element-containing powders with different compositions.
[0041] The metal powder is not limited to the above composition. The metal element contained in the metal powder may be at least one selected from the group consisting of iron (Fe), copper (Cu), titanium (Ti), manganese (Mn), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), tin (Sn), chromium (Cr), niobium (Nb), barium (Ba), strontium (Sr), lead (Pb), silver (Ag), praseodymium (Pr), neodymium (Nd), samarium (Sm), and dysprosium (Dy). The metal powder may further contain elements other than the metal element. The metal powder may contain, for example, carbon (C), oxygen (O), beryllium (Be), phosphorus (P), sulfur (S), boron (B), or silicon (Si).
[0042] The metal powder may be a magnetic powder. The metal powder may be a soft magnetic alloy or a ferromagnetic alloy. The metal powder may be, for example, a magnetic powder consisting of at least one selected from the group consisting of Fe-Si alloy, Fe-Si-Al alloy (Sendust), Fe-Ni alloy (Permalloy), Fe-Cu-Ni alloy (Permalloy), Fe-Co alloy (Permendur), Fe-Cr-Si alloy (electromagnetic stainless steel), Nd-Fe-B alloy (rare earth magnet), Sm-Fe-N alloy (rare earth magnet), Al-Ni-Co alloy (Alnico magnet), and ferrite. The ferrite may be, for example, spinel ferrite, hexagonal ferrite, or garnet ferrite. The metal powder may be a copper alloy such as a Cu-Sn alloy, a Cu-Sn-P alloy, a Cu-Ni alloy, or a Cu-Be alloy. The metal powder may include one of the above elements and compositions, or may include more than one of the above elements and compositions.
[0043] The metal powder may be Fe simple substance. The metal powder may be an alloy containing iron (Fe-based alloy). The Fe-based alloy may be, for example, an Fe-Si-Cr-based alloy or an Nd-Fe-B-based alloy. The metal element-containing powder may be at least one of an amorphous iron powder and a carbonyl iron powder. When the metal powder contains at least one of Fe simple substance and an Fe-based alloy, it is easy to produce a compact having a high space factor and excellent magnetic properties from the compound. The metal powder may be an Fe amorphous alloy.
[0044] As a commercially available Fe amorphous alloy powder, for example, at least one selected from the group consisting of AW2-08, KUAMET-6B2 (all of which are product names manufactured by Epson Atmix Corporation), DAP MS3, DAP MS7, DAP MSA10, DAP PB, DAP PC, DAP MKV49, DAP 410L, DAP 430L, DAP HYB series (all of which are product names manufactured by Daido Steel Co., Ltd.), MH45D, MH28D, MH25D, and MH20D (all of which are product names manufactured by Kobe Steel, Ltd.) may be used.
[0045] <Compound manufacturing method> In the manufacture of the compound, the metal powder and the resin composition (each component constituting the resin composition) are mixed while being heated. For example, the metal powder and the resin composition may be kneaded with a kneader, roll, stirrer, etc. while being heated. By heating and mixing the metal powder and the resin composition, the resin composition adheres to a part or the whole of the surface of the metal element-containing particles constituting the metal powder to cover the metal element-containing particles, and a part or the whole of the epoxy resin in the resin composition becomes a semi-cured product. As a result, a compound is obtained. The compound may be obtained by further adding wax to the powder obtained by heating and mixing the metal powder and the resin composition. The resin composition and the wax may be mixed in advance.
[0046] In the kneading, the metal powder, the epoxy resin, the phenol resin, the hardening accelerator, the siloxane compound, and the coupling agent may be kneaded in a tank. After the metal powder, the siloxane compound, and the coupling agent are charged into the tank and mixed, the epoxy resin, the phenol resin, and the hardening accelerator may be charged into the tank to knead the raw materials in the tank. After the siloxane compound, the epoxy resin, the phenol resin, and the coupling agent are kneaded in the tank, the hardening accelerator may be charged into the tank to further knead the raw materials in the tank. A mixed powder (resin mixed powder) of the epoxy resin, the phenol resin, and the hardening accelerator may be prepared in advance, and then the metal powder, the siloxane compound, and the coupling agent may be kneaded to prepare the metal mixed powder, and then the metal mixed powder and the above-mentioned resin mixed powder may be kneaded.
[0047] The kneading time depends on the type of kneading machine, the volume of the kneading machine, and the amount of compound produced, but is preferably 1 minute or more, more preferably 2 minutes or more, and even more preferably 3 minutes or more. The kneading time is preferably 20 minutes or less, more preferably 15 minutes or less, and even more preferably 10 minutes or less. If the kneading time is less than 1 minute, the kneading is insufficient, the moldability of the compound is impaired, and the degree of hardening of the compound varies. If the kneading time exceeds 20 minutes, for example, the hardening of the resin composition (e.g., epoxy resin and phenolic resin) proceeds in the tank, and the fluidity and moldability of the compound are likely to be impaired. When the raw materials in the tank are kneaded with a kneader while being heated, the heating temperature may be, for example, a temperature at which a semi-cured product of the epoxy resin (epoxy resin in B stage) is generated and the generation of a hardened product of the epoxy resin (epoxy resin in C stage) is suppressed. The heating temperature may be a temperature lower than the activation temperature of the curing accelerator. The heating temperature is, for example, preferably 50° C. or higher, more preferably 60° C. or higher, and even more preferably 70° C. or higher. The heating temperature is preferably 150° C. or lower, more preferably 120° C. or lower, and even more preferably 110° C. or lower. When the heating temperature is within the above range, the resin composition in the tank softens and is likely to coat the surfaces of the metal element-containing particles that make up the metal powder, a semi-cured epoxy resin is likely to be produced, and complete curing of the epoxy resin during kneading is likely to be suppressed.
[0048] [Molded body] The molded article according to the present embodiment may include the above-mentioned compound. The molded article according to the present embodiment may include a cured product of the above-mentioned compound. The molded article may include at least one selected from the group consisting of an uncured resin composition, a semi-cured product of the resin composition (B-stage resin composition), and a cured product of the resin composition (C-stage resin composition). The molded article according to the present embodiment may be used as a sealant for electronic components or electronic circuit boards. According to the present embodiment, cracks in the molded article caused by the difference in thermal expansion coefficient between the metal member of the electronic component or electronic circuit board and the molded article (sealant) can be suppressed.
[0049] The cured product of the compound is a cured product of a resin composition containing a metal powder, an epoxy resin, and a phenol resin, and the content of the metal powder is 90% by mass or more and less than 100% by mass. The bending strength of the cured product at 250°C is 4.6 MPa or more, preferably 4.8 MPa or more, and more preferably 5.0 MPa or more, from the viewpoint of increasing the strength of the cured product. The upper limit of the bending strength is about 10 MPa. The bending modulus of the cured product at 250°C is less than 1.0 GPa, preferably 0.1 GPa or more and less than 1.0 GPa, more preferably 0.2 GPa or more and 0.8 GPa or less, even more preferably 0.3 GPa or more and 0.7 GPa or less, and particularly preferably 0.4 GPa or more and 0.68 GPa or less, from the viewpoint of imparting flexibility to the cured product. The value obtained by dividing the bending strength (MPa) at 250°C by the bending modulus (GPa) at 250°C can be used as an index of the reliability of the cured product. The index is 9.5×10 -3 It is preferable that the value is 10×10 or more. -3 More preferably, it is 10.5×10 -3 The upper limit of the index is not particularly limited, and is, for example, 5×10 -2 It may be the following.
[0050] <Method of manufacturing molded body> The method for producing a molded body according to the present embodiment may include a step of pressurizing the compound in a mold. The method for producing a molded body may include a step of pressurizing the compound covering a part or the entire surface of the metal member in a mold. The method for producing a molded body may include only the step of pressurizing the compound in a mold, or may include other steps in addition to the step. The method for producing a molded body may include a first step, a second step, and a third step. Each step will be described in detail below.
[0051] In the first step, a compound is prepared by the method described above.
[0052] In the second step, the compound is pressed in a mold to obtain a molded body (B-stage molded body). In the second step, the compound covering a part or the whole surface of the metal member may be pressed in a mold to obtain a molded body (B-stage molded body). In the second step, the resin composition is filled between the individual metal element-containing particles constituting the metal element-containing powder. The resin composition functions as a binding material (binder) to bind the metal element-containing particles to each other.
[0053] In the second step, transfer molding of the compound may be performed. In the transfer molding, the compound may be pressurized at 5 MPa or more and 50 MPa or less. The higher the molding pressure, the easier it is to obtain a molded body with excellent mechanical strength. In consideration of the mass productivity of the molded body and the life of the mold, the molding pressure is preferably 8 MPa or more and 20 MPa or less. The density of the molded body formed by transfer molding may be preferably 75% or more and 86% or less, more preferably 80% or more and 86% or less, based on the true density of the compound. When the density of the molded body is 75% or more and 86% or less, a molded body with excellent mechanical strength is easily obtained. In the transfer molding, the second step and the third step may be performed at the same time.
[0054] In the third step, the molded body is cured by heat treatment to obtain a molded body in the C stage. The heat treatment temperature may be any temperature at which the resin composition in the molded body is sufficiently cured. The heat treatment temperature may be preferably 100°C or more and 300°C or less, more preferably 110°C or more and 250°C or less. In order to suppress oxidation of the metal powder in the molded body, it is preferable to perform the heat treatment in an inert atmosphere. When the heat treatment temperature exceeds 300°C, the metal powder is oxidized or the resin cured product is deteriorated by a trace amount of oxygen inevitably contained in the heat treatment atmosphere. In order to sufficiently cure the resin composition while suppressing oxidation of the metal powder and deterioration of the resin cured product, the heat treatment temperature may be held for preferably several minutes or more and 10 hours or less, more preferably 3 minutes or more and 8 hours or less. EXAMPLES
[0055] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples in any way.
[0056] Details of each component used in preparing the compounds of the examples and comparative examples are given below. (First epoxy resin) Biphenylene aralkyl type epoxy resin (product name: NC-3000, manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent: 275 g / eq) (Second epoxy resin) Multifunctional epoxy resin (Product name: TECHMORE VG3101L, manufactured by Printec Co., Ltd., epoxy equivalent: 215g / eq) Triphenylmethane type multifunctional epoxy resin (EPPN-501HY manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent: 169g / eq) Orthocresol novolac epoxy resin (DIC Corporation product name: EPICLON N-500P-2, epoxy equivalent: 202g / eq)
[0057] (First phenolic resin) Biphenylene aralkyl type phenolic resin (product name: MEHC-7851SS, manufactured by Meiwa Kasei Co., Ltd., hydroxyl group equivalent: 202 g / eq) Biphenylene aralkyl phenolic resin (product name: MEHC-7841-4S, manufactured by Meiwa Kasei Co., Ltd., hydroxyl equivalent: 166g / eq) (Second phenolic resin) Triphenylmethane type phenolic resin (Air Water Inc. product name: HE910-09, hydroxyl equivalent: 101g / eq) Novolac phenolic resin (Hitachi Chemical Co., Ltd. product name: HP-850N, hydroxyl equivalent: 103g / eq)
[0058] (Cure accelerator) Urea-based curing accelerator (product name: U-CAT 3512T, manufactured by San-Apro Co., Ltd.) (Coupling Agent) Methacryloxyoctyltrimethoxysilane (product name: KBM-5803, manufactured by Shin-Etsu Chemical Co., Ltd.) 3-Mercaptopropyltrimethoxysilane (trade name: KBM-803, manufactured by Shin-Etsu Chemical Co., Ltd.) (Siloxane compounds) Caprolactone-modified dimethyl silicone (trade name: DBL-C32, manufactured by Gelest Co., Ltd.) (Release agent) Zinc laurate (product name: Powder Base L, manufactured by NOF Corporation) Partially saponified Montan acid ester wax (product name: LICOWAX OP, manufactured by Clariant Chemicals Co., Ltd.)
[0059] (metal powder) Amorphous iron powder (Epson Atmix Corporation product name: 9A4-II, average particle size 24 μm) Amorphous iron powder (Epson Atmix Corporation product name: AW2-08, average particle size 5.3 μm)
[0060] [Preparation of compound] (Examples 1 to 3) The epoxy resin, phenolic resin, curing accelerator, and release agent shown in Table 1 were placed in a plastic container in the amounts (unit: g) shown in the same table. These materials were mixed in the plastic container for 10 minutes to prepare a resin mixture. The resin mixture corresponds to all components of the resin composition except for the siloxane compound and the coupling agent.
[0061] Two kinds of amorphous iron powders shown in Table 1 were mixed uniformly for 5 minutes in a pressurized twin-screw kneader (manufactured by Nippon Spindle Manufacturing Co., Ltd., capacity 5 L) to prepare metal powder. The coupling agent and siloxane compound shown in Table 1 were added to the metal powder in the twin-screw kneader. Then, the contents of the twin-screw kneader were heated to 90°C, and the contents of the twin-screw kneader were mixed for 10 minutes while maintaining the temperature. Then, the above resin mixture was added to the contents of the twin-screw kneader, and the contents were melted and kneaded for 15 minutes while maintaining the temperature of the contents at 120°C. The kneaded product obtained by the above melting and kneading was cooled to room temperature, and then crushed with a hammer until the kneaded product had a predetermined particle size. The above "melt" means that at least a part of the resin composition in the contents of the twin-screw kneader is melted. The metal powder in the compound does not melt during the preparation process of the compound. The compounds of Examples 1 to 3 were prepared by the above method.
[0062] (Comparative Examples 1 to 5) Compounds of Comparative Examples 1 to 5 were prepared in the same manner as in the Examples, except that the types and amounts of each component were changed as shown in Table 2.
[0063] [Compound evaluation] The compounds obtained in the Examples and Comparative Examples were evaluated as follows. The results are shown in Tables 1 and 2.
[0064] (Liquidity) The fluidity was evaluated using a flow tester CFT-100 manufactured by Shimadzu Corporation. 7 g of the compound was molded to prepare a tablet. Using the tablet, the fluidity was evaluated under the conditions of 130°C, preheating for 20 seconds, and a load of 100 kg. The plunger's pushing distance (unit: mm) until the compound stopped flowing was defined as the flow tester stroke, and the time until the compound stopped flowing was measured as the flow time, which was used as an index of fluidity.
[0065] (Gel Time) The gel time of the compound was measured by the following method. Using a Curelastometer (manufactured by JSR Trading Co., Ltd.), the gel time was measured under the conditions of a sample amount of 1.5 mL and 140°C. The time at which the torque on the obtained chart started to rise was taken as the gel time. The shorter the gel time, the higher the curability.
[0066] (Bending test) The compound was transfer molded under the conditions of a mold temperature of 140°C, molding pressure of 13.5 MPa, and curing time of 360 seconds, and then post-cured at 180°C for 2 hours to obtain a test specimen. The dimensions of the test specimen were 80 mm length x 10 mm width x 3.0 mm thickness.
[0067] Using an autograph equipped with a thermostatic chamber, a three-point support bending test was carried out on the test specimen at room temperature and at 250°C. The autograph used was an AGS-500A manufactured by Shimadzu Corporation. In the bending test, one side of the test specimen was supported by two supports. A load was applied to the center position between the two supports on the other side of the test specimen. The load at which the test specimen broke was measured. The measurement conditions for the bending test were as follows: Distance between two supports Lv: 64.0±0.5mm Head speed: 2.0±0.2mm / min Chart speed: 100mm / min Chart full scale: 490N (50kgf)
[0068] The bending strength σ (unit: MPa) was calculated based on the following formula (A). The bending modulus E (unit: GPa) was calculated based on the following formula (B). In the formulas below, "P" is the load (unit: N) when the test piece breaks. "Lv" is the distance between two supports (unit: mm). "W" is the width of the test piece (unit: mm). "t" is the thickness of the test piece (unit: mm). "F / Y" is the gradient of the straight line portion of the load-deflection curve (unit: N / mm). σ = (3 × P × Lv) / (2 × W × t 2 ) (A) E=[Lv 3 / (4×W×t 3 )]×(F / Y) (B)
[0069] (Reliability) The reliability evaluation index was determined by dividing the bending strength (MGa) at 250° C. by the bending modulus (GPa) at 250° C. The larger this value, the better the balance between strength and modulus.
[0070] (Reflow processing) A copper metal member was sealed with a compound by transfer molding, and the compound was hardened to obtain a molded body. The molded body was subjected to a reflow treatment. The maximum heating temperature in the reflow treatment was 260°C. The heating time was 300 seconds. After the reflow treatment, the molded body was observed to check whether or not there were cracks in the molded body. "A" in the table means that no cracks were formed in the molded body, and "B" means that cracks were formed in the molded body.
[0071] [Table 1]
[0072] [Table 2]
Claims
1. The present invention comprises a metal powder and a resin composition containing an epoxy resin and a phenolic resin, the epoxy resin comprises a first epoxy resin having a biphenylene aralkyl skeleton and a second epoxy resin having an epoxy equivalent smaller than that of the first epoxy resin, the phenol resin includes a first phenol resin having a biphenylene aralkyl skeleton and a second phenol resin having a hydroxyl group equivalent smaller than that of the first phenol resin, The compound, wherein the metal powder contains at least one of simple Fe and an Fe-based alloy, and the content of the metal powder is 90 mass % or more and less than 100 mass %.
2. 2. The compound according to claim 1, wherein the epoxy equivalent of the first epoxy resin is from 240 g / eq to 300 g / eq.
3. The compound according to claim 1 or 2, wherein the hydroxyl equivalent of the first phenolic resin is 140 g / eq or more and 230 g / eq or less.
4. The compound according to any one of claims 1 to 3, wherein the content of the first epoxy resin is 20 to 80 mass% based on the total mass of the epoxy resins.
5. A molded body comprising the compound according to any one of claims 1 to 4.
6. A cured product of a compound comprising a metal powder and a resin composition containing an epoxy resin and a phenolic resin, The metal powder contains at least one of Fe elemental element and Fe-based alloy, and the content of the metal powder is 90 mass% or more and less than 100 mass%, The bending strength at 250° C. is 4.6 MPa or more, the bending modulus at 250° C. is less than 1.0 GPa, and the value obtained by dividing the bending strength by the bending modulus is 9.5×10 -3 This is the hardened compound.
Citation Information
Patent Citations
Highly heat conductive epoxy resin composition and semiconductor device
JP2004292515A
Highly heat-conductive epoxy resin composition and semiconductor device
JP2004300214A
Epoxy resin composition and electronic component device
JP2014005359A
inductor
JP2014013803A
Cured article of resin composition, resin composition and multilayer substrate
JP2017179351A